2007
DOI: 10.1016/j.schres.2006.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Increased hemodynamic response in the hippocampus, thalamus and prefrontal cortex during abnormal sensory gating in schizophrenia

Abstract: Objective-Deficits in sensory gating are a common feature of schizophrenia. Failure of inhibitory gating mechanisms, shown by poor suppression of evoked responses to repeated auditory stimuli, have been previously studied using EEG methods. These methods yield information about the temporal characteristics of sensory gating deficits, but do not identify brain regions involved in the process. Hence, the neuroanatomical substrates of poor sensory gating in schizophrenia remain largely unknown. This study used fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
100
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(115 citation statements)
references
References 37 publications
14
100
1
Order By: Relevance
“…That is, activation in such a network should increase with increasing P50 suppression. An indirect approach to this issue used a comparison between the fMRI-BOLD response to nine click repetitions, separated by 500 ms, with that to a single click, in a group of schizophrenic patients as well as in controls (Tregellas et al, 2007). EEG P50 suppression was reduced in the patients but, contrary to expectations, the BOLD response in a network consisting of dorsolateral prefrontal cortex, hippocampus, and thalamus, was increased.…”
Section: Box 4 Human Electrophysiology As Indices Of a 'Unified Brainmentioning
confidence: 97%
“…That is, activation in such a network should increase with increasing P50 suppression. An indirect approach to this issue used a comparison between the fMRI-BOLD response to nine click repetitions, separated by 500 ms, with that to a single click, in a group of schizophrenic patients as well as in controls (Tregellas et al, 2007). EEG P50 suppression was reduced in the patients but, contrary to expectations, the BOLD response in a network consisting of dorsolateral prefrontal cortex, hippocampus, and thalamus, was increased.…”
Section: Box 4 Human Electrophysiology As Indices Of a 'Unified Brainmentioning
confidence: 97%
“…Indeed, there are several reports on enhanced activity of brain areas involved in the pathophysiology of schizophrenia under conditions of limited cognitive load. For example, one study found greater activation in the hippocampus, thalamus, and dorsolateral prefrontal cortex in patients with schizophrenia during the sensory gating task and in response to urban noise (Tregellas et al, 2007(Tregellas et al, , 2009, whereas another group reported on the elevated hippocampal and amygdala activity during the passive viewing of human faces (Holt et al, 2006). However, when the behavioral performance sets additional demands on these networks, activity will increase further, and such an above-physiological increase will now be accompanied by abnormally high or lost synchronization, phenomena also observed after short-term application of sufficiently high doses of PCP-like drugs (Sebban et al, 2002;Pinault, 2008).…”
Section: Mglu2/3 Receptor Agonistsmentioning
confidence: 99%
“…P50 sensory gating is thought to reflect a complex interaction of inhibitory neurocircuits located primarily in the hippocampus, dorsolateral prefrontal cortex, and thalamus 16 . Thus, alterations in P50 sensory gating in infants may suggest altered development in these regions of the brain.…”
Section: Discussionmentioning
confidence: 99%